Gene‐environment interaction of genome‐wide association study‐identified susceptibility loci and meat‐cooking mutagens in the etiology of renal cell carcinoma. Issue 1 (9th November 2015) - Melkonian, Stephanie C.; Daniel, Carrie R.; Ye, Yuanqing; Tannir, Nizar M.; Karam, Jose A.; Matin, Surena F.; Wood, Christopher G.; Wu, Xifeng
Abstract : BACKGROUND: Meat‐cooking mutagens may be associated with renal cell carcinoma (RCC) risk. In the current study, the authors examined associations between meat‐cooking mutagens, genetic susceptibility variants, and risk of RCC. METHODS: The authors used 659 newly diagnosed RCC cases and 699 healthy controls to investigate the association between dietary intake of meat‐cooking mutagens and RCC. They examined whether associations varied by risk factors for RCC and genetic susceptibility variants previously identified from genome‐wide association studies. Odds ratios and 95% confidence intervals were estimated using tertiles of intake of dietary polycyclic aromatic hydrocarbons/heterocyclic amines. RESULTS: Dietary intake of the mutagenic compounds 2‐amino‐3, 8‐dimethylimidazo‐(4, 5‐f) quinoxaline (MeIQx) and 2‐amino‐1 methyl‐6‐phenylimidazo(4, 5‐b)pyridine (PhIP) were found to be significantly associated with an increased risk of RCC (odds ratios across tertiles: 1.00 [referent], 1.28 [95% confidence interval, 0.94‐1.74], and 1.95 [95% confidence interval, 1.43‐2.66] [ P for trend <.001], respectively; and 1.00 [referent], 1.41 [95% confidence interval, 1.04‐1.90], and 1.54 [95% confidence interval, 1.14‐2.07] [ P for trend =.02], respectively). The authors observed evidence of interactions between PhIP and RCC susceptibility variants in 2 genes: inositol 1, 4, 5‐trisphosphate receptor, type 2 ( ITPR2 ) (rs718314; multiplicative P for interaction = .03 and additive P for interaction =.002) and endothelial PAS domain‐containing protein 1 ( EPAS1 ) (rs7579899; additive P for interaction =.06). CONCLUSIONS: The intake of meat may increase the risk of RCC through mechanisms related to the cooking compounds MeIQx and PhIP. These associations may be modified by genetic susceptibility to RCC. Further research is necessary to understand the biological mechanisms underlying these interactions. Cancer 2016;122:108–115. © 2015 American Cancer Society . Abstract : The results of the current study indicate that the intake of meat may increase the risk of renal cell carcinoma through mechanisms related to the cooking compounds MeIQx and PhIP. These associations may be modified by genetic susceptibility to renal cell carcinoma.